Cerebral Ischemic Reperfusion Injuries (CIRI) Bench Research and Clinical Implications (Springer Series in Translational Stroke Research,, 2018)
This volume is focused on subjects related to cerebral ischemia and reperfusion injuries after acute stroke. All chapters are selected from the Sixth Elite Stroke meeting named Pangu Stroke Conference and written by members of world leading laboratories of stroke studies. The contents cover both clinical and bench studies, from basic components of cerebral arterial system to clinical reperfusion injury cases, from reperfusion caused programmed cell death and astrocyte activation to oxidative stress and nitric oxide after reperfusion, from extracellular matrix and inflammation to a role of diabetes after reperfusion, from small artery disorders to collateral circulation and blood pressure control after reperfusion. Wei-Jian Jiang, Chairman of New Era Stroke Care and Research Institute of PLA Rocket Force General Hospital, Beijing, China. Wengui Yu, Professor and Director of Comprehensive Stroke & Cerebrovascular Center, University of California, Irvine Yan Qu, Professor and Director of Neurosurgery at the Second Affiliated Hospital of Air Force Medical University, Xi'an, China. Zhongsong Shi, Professor of Neurosurgery at Sun Yat-sen Memorial Hospital, Sun Yat-sen University, Guangzhou, China. Ben-yan Luo, Professor and Chair of Neurology at the First Affiliated Hospital of Zhejiang University. John H. Zhang, Professor of Anesthesiology and Physiology at Loma Linda University School of Medicine, Loma Linda, CA, USA.